Implementasi Metode Pembelajaran Inside-Outside Circle Dalam Meningkatkan Hasil Dan Ketuntasan Belajar Siswa Pada Mata Pelajaran Tik Kelas VIII Smp N 2 Batang - Arbiyanti, Yossi Norma; Suryono, Suryono (Edu Komputika Journal, 2017)
The aims of the study are to know how much improving learning outcomes of student in ICT learning with the implementation of Inside-outsdie Circle methods, to know how much the changes increase mastery learning of student, subsequent to the learning process improvement using Inside-outside Circle methods. This type of research is experimental, while the design of the study is a quasi experimental design model pretest-posttest control group design. Sampling was done by random sampling techniques, students of class VIII C as a experimental class and class VIII D as the control class. The results showed that the mean score of pretest class VIII C (experimental class) 57.22 and the mean score of posttest was 75.09, it meant that the students’ achievement was improved by 17.87. As for the class VIII D (control class) the mean score of pretest was 54.11 and the posttest mean score was 67.50, it meant that it was improved by 13.39. Percentage of mastery learning showed 54% of students completed KKM in class VIII C (experimental class) and 19% of students completed KKM in class VIII D (control class), percentage mastery learning of students achievement was improved by 35%. Based on the explanation above, it can be concluded that the learning Inside-outside Circle (IOC) methods can improve outcomes and mastery learning of students on ICT in class VIII SMP N 2 Batang.